Problems and trends in water resources management in Yusufiya district - Al- Zobaei, Amir Nima Mohammed; Al-Dulaimi, Kasim Ahmed Remal (Al-Adab Journal, 2021)
The study dealt with water resources in the Yusufiya sub-district and ways to manage them, which is one of the most important agricultural areas in the Baghdad governorate within the Mahmoudiya district, located astronomically between two latitude circles (00 = 3 - 33 o - 00 = 12 - 33o) in the north, and between longitudes (00 = 0- 44 o- 00 = 18- 44 o) to the east, with an area of ​​425 km2. The study focused on a very important problem facing the side, namely (mismanagement of water resources) and the associated phenomena of waste and pollution, which are among the most important internal risks that threaten the water security of the citizen, as the study showed ways to manage water at the local level. The study found that there are human problems that affected the management of water resources in the region, the most important of which were the mismanagement of the water system, the large increase in population numbers, pollution and the excess of 418 fish lakes, with a water area estimated at about (1524.5) dunums, and with an annual water consumption of about (370960). 3) m3 / year, unlicensed water pumps whose annual water consumption reaches (2226500) m3 / year, and the use of the traditional (Sihi) irrigation system, which leads to the loss of 50% of the water, as well as unjustified waste and waste by the population. The Water Evaluation and Planning System (WEAP) was also introduced into operation, as this system bore fruit in the countries that worked in it, as it was through it that the amount of water needs was estimated with the aim of covering and providing them to ensure sustainable development and water management in the region. The region needs to provide about (242.13) million m3 / year of water in 2020, to increase in the year 2025 to about (348.04) million m3 / year, and then to (454.05) million m3 / year in 2030.